The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1002/mbo3.506
|View full text |Cite
|
Sign up to set email alerts
|

The viable but nonculturable state induction and genomic analyses of Lactobacillus casei BM‐LC14617, a beer‐spoilage bacterium

Abstract: This study aimed to investigate the viable but nonculturable (VBNC) state and genomic features of a beer‐spoilage strain, Lactobacillus casei BM‐LC14617. Induction on the VBNC state of L. casei strain BM‐LC14617 was conducted by both low‐temperature storage and continuous passage in beer, and formation of VBNC state was detected after 196 ± 3.3 days and 32 ± 1.6 subcultures, respectively. Resuscitation of VBNC cells was successfully induced by addition of catalase, and culturable, VBNC, and resuscitated cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…It was also found that the culturability of L. brevis declined significantly during conditions induced by beer subculture or low temperature, indicating the VBNC L. brevis could be potentially neglected in brewery environments due to incapability of detection by traditional culture methods. As Lactobacillus strains were concerned, up to date, a total of five species have been validated for VBNC state formation, including L. lindneri ( Suzuki et al, 2006 ; Liu et al, 2017a ), L. casei ( Liu et al, 2017c ), L. plantarum ( Liu et al, 2017b ), L. paracollinocides , ( Suzuki et al, 2006 ) and L. acetotolerans ( Deng et al, 2015 ), which had been induced to enter into VBNC state by either low-temperature storage or beer subculture treatment. Consequently, this is the first the formation and recovery of VBNC state by the species of L. brevis as the most common beer spoilage and hop resistance strain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that the culturability of L. brevis declined significantly during conditions induced by beer subculture or low temperature, indicating the VBNC L. brevis could be potentially neglected in brewery environments due to incapability of detection by traditional culture methods. As Lactobacillus strains were concerned, up to date, a total of five species have been validated for VBNC state formation, including L. lindneri ( Suzuki et al, 2006 ; Liu et al, 2017a ), L. casei ( Liu et al, 2017c ), L. plantarum ( Liu et al, 2017b ), L. paracollinocides , ( Suzuki et al, 2006 ) and L. acetotolerans ( Deng et al, 2015 ), which had been induced to enter into VBNC state by either low-temperature storage or beer subculture treatment. Consequently, this is the first the formation and recovery of VBNC state by the species of L. brevis as the most common beer spoilage and hop resistance strain.…”
Section: Resultsmentioning
confidence: 99%
“…If beer contaminated by VBNC strains has been delivered to commercial markets, even small numbers of hop-resistance bacteria will recover and eventually impart off-flavor and turbidity to beer. Up to date, five species of Lactobacillus strains have been verified for formation of VBNC state, including L. lindneri ( Suzuki et al, 2006 ; Liu et al, 2017a ), L. casei ( Liu et al, 2017c ), L. plantarum ( Liu et al, 2017b ), L. paracollinocides ( Suzuki et al, 2006 ) and L. acetotolerans ( Deng et al, 2015 ), which had been induced to enter into the VBNC state by beer subculture treatment or low-temperature storage.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the VBNC formation and identification, rapid detection of the VBNC state of MRSA is of urgent necessity and importance, along with the formation of the VBNC state ( Liu et al, 2016c , 2017a , b , c ). In this study, formation of the VBNC state has been performed on MRSA strains, then development and evaluation of an isothermal nucleic acid amplification-based propidium monoazide (PMA) detection assay have been conducted on MRSA.…”
Section: Introductionmentioning
confidence: 99%
“…To validate the existent bacteria, the genomic DNA of bacterial cells from the spoiled beer sample and the isolated L. harbinensis cells were extracted by bacterial genomic DNA extraction kit (Sigma-Aldrich, USA) and subjected to genomic sequencing by Illumina HiSeq. 2500 platform and paired-end libraries, respectively 10 , 47 . Sequences were quality processed using the FastQC pipeline v.0.10.1 before assembly.…”
Section: Methodsmentioning
confidence: 99%